FAMILY DITOMYIIDAE - Falaschi, Rafaela Lopes (Zootaxa, 2016)
The Ditomyiidae are a family belonging to the suborder Bibionomorpha, until now without records to Colombia. This work reports the first record of the genera Rhipidita and Calliceratomyia for the Colombian region.